Réponses

2013-05-22T16:46:11+02:00

 3x + 2 = 2x - 5

          x = - 7

 

-5x + 4 = 6x + 8

      11x = -4

           x = -4/11

 

-4(3 + x) = 2x - 6

  -12 - 4x = 2x - 6

          -6x = 6

             x = -1

 

  7x = 2 - 3x

10x = 2

     x = 1/5

  • Utilisateur Brainly
2013-05-22T17:28:14+02:00

3x+2=2x-5

3x+2-2x=2x-5-2x

1x+2=-5

1x+2-2=-5-2

1x=-7

x=-7/1

x=-7

 

-5x+4=6x+8

-5x+4-6x=6x+8-6x

-11x+4=8

-11x+4-4=8-4

-11x=4

x=4/-11

 

-4(3+x)=2x-6

-4*3-4*x=2x-6

-12-4x=2x-6

-12-4x-2x=2x-6-2x

-12-6x=-6

-12-6x+12=-6+12

-6x=6

x=6/-6

x=-1

 

 

7x=2-3x

7x+3x=2-3x+3x

10x=2

x=2/10

x=0.2

 

voilà...... :)